The Theoretical Construction of Pobladores and Favelados as Social Movements in Latin America. - Cortés, Alexis (Latin American Research Review, 2021)
How did the social sciences theoretically contribute to producing the movements of Chilean pobladores and Brazilian favelados during the twentieth century? Through a critical review of the main theories that seek to understand the political actions of the urban poor in Santiago de Chile and Rio de Janeiro, this article shows the close relationship between these movements and the production of social sciences, in which a double hermeneutic operates—a mutually influential reflexive process that eventually contributed to the constitution and recognition of the movements as such. This research analyzes how social sciences perform the same social struggles that they attempt to describe, in other words, how certain academic contexts interact positively or negatively with the political and social disputes generated from the movements in question. I review theories of marginality and dependent urbanization, urban social movements, utilitarian views, and new social movements, showing how these interpretations alternated between requiem, rediscovery, and denial of the favelados and pobladores as social movements.